Uma sequência didática proposta para o ensino de funções na escola bilíngue para surdos - Zanoni, Graziely Grassi (2016)
The math subject is shown in a formal, abstract and deductive way at school , so, to understand the math concepts, it is important to teach considering the own characteristics of this subject. For the deaf people, it is reinforced, because they use two linguistic representations to communicate. Besides understanding the math language, there is the need to move from Portuguese language to the sign language and vice-versa for the learning of the math concepts that are being taught. The aim of this study was to understand the use of didactic sequences in the teaching process of functions for deaf students. It was a qualitative research, research-action type that, after appropriate bibliographic search and interview with the subjects of the research to choose the concept to be worked, a didactic sequence was elaborated and applied to deaf students in a bilingual school in west region of Paraná, proposing teaching situation in which high school deaf students from regular school, were challenged to write the required math expression. To collect the data, the process was filmed while the units that made the didactic sequences were applied, not only to register the speech using the sign language between the researcher and the students, but also to register the written representation done by the students. As a result, the group discussions and interactions brought about important contributions to teaching and learning process of written function concept. In the teaching view, the researcher used text in Portuguese language and pictures to build the unit that formed the didactic sequence and noticed, during the research process, the difficulty in understanding the written text to solve the unit and, also difficulty in matching the texts elements related to math proposed in the unit and, that they needed other information related to the pictures to establish the required relations. From the learning view, there were advances in relation to the first representations forms in arithmetic mode to the algebra expression. In the representation, using tables, from the relation between the proposed variable in the unit, they showed up like columns of numbers without reference, although everybody was in high school. One of the students showed the meaning of operational function through math algebraic expression, explaining the independent relation between the variables. The research showed that the didactic sequence planned assist the teaching process not only for deaf students, since the differential between them and the listener ones require an extra representation to the math knowledge access, the sign language and it is essential to mention that the use of different visual representation is important for the teaching of math concepts to deaf students